TINJAUAN KRIMINOLOGI TERHADAP SENSUAL MARKETING SEBAGAI STRATEGI PEMASARAN PRODUK YANG DIPERANKAN OLEH SALES PROMOTION GIRL DI KOTA PEKANBARU - Munir, Abdul; Wahyudi, Septian; Zainal, Zainal (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2020)
This study tries to describe the phenomenon of exploitation of women's bodies in product marketing business activities (cars and cigarettes) played by SPG in Pekanbaru. The exploitation of the body is a consequence of the product marketing system in the business world through a "sensual marketing" approach to steal consumer sympathy by constructing a woman's body (SPG) through a sexy and active appearance. This study uses a critical social theory approach "Class Struggle" as a macro theory, and is followed by a "Victim" theory as a micro theory in its analysis chapter. Furthermore, this research method uses an approach in obtaining data, through unstructured in-depth interviews with various parties involved in procuring field data. From the results of the research that the author has described above, this research can be gathered with as is well known,SPG is a female saleswoman who offers services to serve customers. The use of SPG is based on intense competition between similar products. Let's say that cigarette products are one of the products that always use SPG services, because the level of public consumerism towards cigarettes is very high, cigarette manufacturers have started to make several variants of cigarette products to increase the purchasing power of these cigarette products